Conceptual Art and Post-Conceptual. The Idea as Art: Duchamp, Beuys, Cage and Fluxus - Vásquez Rocca, Adolfo (Nómadas. Critical Journal of Social and Juridical Science, 2013)
In conceptual art the idea or concept takes precedence over the material realization of the work and the same process-notes, sketches, models, dialogues-to be often more important than the finished object can be exposed to show the origin and development of the thought initial. The true work of art is the idea. Conceptual art is an art critic and corrosive stresses mental, in the conception of works, relegating its importance or sensitive material realization. Along with this reductionism of the manual exists in a conceptual artwork art work overvaluation as a reflective activity, both mental and experiential. Conceptual artists advocate outright rejection of consumption commercial aspects of art and at the same time, many of them trying to ingrain his artistic activity in a broader context of social concerns, environmental and intellectual, as opposed to the production of objects designed utilitarian and functional criteria to the cultural establishment.